(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2015)
Destination management organizations (DMO) are considered to be the most important entities that are responsible for the promotion and development of tourism in a given area. In view of the above, these entities are assigned numerous tasks and responsibilities, and they are provided with a variety of instruments for the realization of specific goals. Apart from the traditional tasks that are assigned to the DMO (i.e. promotion), increasing attention is being paid to other marketing activities including those related to the creation and commercialization of tourist products. The present article covers an analysis of the DMO operations related to the development of tourist products. It contains both theoretical deliberations related to the DMO and its scope of responsibilities, as well as the results of the author’s own research concerning the issue in question.